2000
DOI: 10.1074/jbc.275.6.4383
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Factor-κB-mediated Transcription by Association with the Amino-terminal Enhancer of Split, a Groucho-related Protein Lacking WD40 Repeats

Abstract: The amino-terminal enhancer of split (AES) encodes a 197-amino acid protein that is homologous to the NH 2 -terminal domain of the Drosophila Groucho protein but lacks COOH-terminal WD40 repeats. Although the Drosophila Groucho protein and its mammalian homologs, transducin-like enhancer of split proteins, are known to act as non-DNA binding corepressors, the role of the AES protein remains unclarified. Using the yeast twohybrid system, we have identified the protein-protein interaction between AES and the p65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 50 publications
2
102
1
Order By: Relevance
“…Yeast Y190 cells were co-transformed with expression vectors encoding various Cdc25C proteins fused to Gal4 DNA-binding domain and pACT2-PCNA expressing PCNA fused to Gal4 activation domain. These transformants were streaked on selective medium lacking leucine and tryptophan, allowed to grow for 2 days at 308C and tested for b-galactosidase activity using X-gal colony ®lter assay as described previously (Yang et al, 1999;Tetsuka et al, 2000). Hatched box (1 ± 40) indicates the minimal PCNA interaction region of Cdc25C obtained by this analysis.`+', positive for b-galactosidase activity;`itself', auto-activation of Lac Z reporter gene in Y190;`ND', not determined Thus, we further examined the speci®city of interaction by creating various Cdc25C deletion mutants and tested the interaction with PCNA by yeast two-hybrid system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast Y190 cells were co-transformed with expression vectors encoding various Cdc25C proteins fused to Gal4 DNA-binding domain and pACT2-PCNA expressing PCNA fused to Gal4 activation domain. These transformants were streaked on selective medium lacking leucine and tryptophan, allowed to grow for 2 days at 308C and tested for b-galactosidase activity using X-gal colony ®lter assay as described previously (Yang et al, 1999;Tetsuka et al, 2000). Hatched box (1 ± 40) indicates the minimal PCNA interaction region of Cdc25C obtained by this analysis.`+', positive for b-galactosidase activity;`itself', auto-activation of Lac Z reporter gene in Y190;`ND', not determined Thus, we further examined the speci®city of interaction by creating various Cdc25C deletion mutants and tested the interaction with PCNA by yeast two-hybrid system.…”
Section: Resultsmentioning
confidence: 99%
“…Human cDNA library from an osteosarcoma cell line for the yeast two-hybrid screening was obtained commercially (Matchmaker cDNA Library, Clontech). Screening was performed according to the supplier's protocol using yeast strain Y190 as described previously (Yang et al, 1999;Tetsuka et al, 2000;Uranishi et al, 2001). For the subsequent two-hybrid assays to examine the protein ± protein interaction in the yeast, the pAS2-1 plasmids expressing various portions of Cdc25C (as described in Figure 1) were transfected into the yeast together with pACT2 ± PCNA, expressing PCNA fused to Gal4 activation domain, and detected the expression of b-galactosidase enzyme activity to con®rm the speci®c interaction.…”
Section: Yeast Two-hybrid Screenmentioning
confidence: 99%
“…11,12 Gro/TLEs inhibit NF-kB signaling, a pathway for inflammation and proliferation of inflammatory cells. 13 Although most of these related studies reported that the Groucho/TLE family of corepressors inhibits gene expression and the signaling pathway, it also enhances the gene expression including the macrophage colony stimulating factor receptor, 14 Notch ligand Jagged1, 15 and Wnt pathway mediator plakoglobin. 16 The Groucho/ TLE family of corepressors was also suggested to be an oncogene because the over-expression of Gro/TLE family members is associated with lung adenocarcinoma, 17 grade 1 astrocytomas, 18 higher-grade meningiomas, 19 pituitary adenomas, 20,21 and synovial sarcomas, 7,22 which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the other subgroup, e.g., Grg5 in mice and AES in humans, contain the amino-terminal region of gro, including the Q-rich domain, but lack most of the variable region and the entire WD-40 repeat region. Mammalian gro homologues in the first group bind to transcription factors that target gene repression (Aronson et al, 1997;Roose et al, 1998;Eberhard et al, 2000;Tetsuka et al, 2000;Wang et al, 2000;Brantjes et al, 2001), whereas the short form of gro, such as XGrg5 in Xenopus, has been shown to enhance transcriptional activity (Roose et al, 1998;Brantjes et al, 2001). It has been speculated that Grg5 may act as a dominant negative molecule within a transcription complex.…”
Section: Introductionmentioning
confidence: 99%